Antimicrobial Resistance Surveillance of Pigs and Chickens in the Lao People's Democratic Republic, 2018-2021 - Phouth Inthavong; Somphaivanh Chanthavong; Phounsavanh Nammanininh; Phouvong Phommachanh; Watthana Theppangna; Agnes Agunos; Jaap A. Wagenaar; Bounlom Douangngeun; Leo Loth (MDPI AG, 2022)
The use of antimicrobials in the livestock sector has been identified as a driver for the emergence of antimicrobial resistance (AMR), and AMR has become a growing public health and economic threat in the Lao PDR. We conducted surveillance for AMR in five provinces of the Lao PDR, in order to determine the antimicrobial susceptibility of Escherichia coli and Salmonella spp. isolated from caecal samples from slaughtered pigs at slaughterhouses and from slaughtered chickens at markets during two different time periods: 2018/2019 and 2020/2021. Antimicrobial susceptibility was determined using a panel of 14 antimicrobials using the broth microdilution technique. E. coli and Salmonella from chickens (62% and 33%, respectively) and pigs (88% and 81%, respectively) exhibited resistance to ≥3 classes of antimicrobials. Of important public health concern was the detection of Salmonella resistant to cefotaxime/ceftazidime, ciprofloxacin, and colistin, deemed as critically important antimicrobials in human medicine. This study aimed to evaluate a national sampling strategy at slaughterhouses and wet markets, and to pilot the laboratory methodologies for bacterial recovery and AMR testing. Experiences from this study will inform capacity development for a national AMR surveillance program, and these early data could serve as reference points for monitoring the impact of the Lao PDR's national action plan to contain AMR.